Transfer of airway skills from manikin training to patient: success of ventilation with facemask or LMA‐SupremeTM by medical students. (19th August 2013) - Russo, S. G.; Bollinger, M.; Strack, M.; Crozier, T. A.; Bauer, M.; Heuer, J. F.
Summary During emergency care, the ability to ventilate the patient's lungs is a crucial skill. Supraglottic airway devices have an established role in emergency care, and manikin trials have shown that placement is easy even for inexperienced users. However, there is current discussion as to what extent these results can be transferred to patients. We studied the transfer of skills learnt on a manikin to the clinical situation in novice medical students during their anaesthesia rotation. They were required to ventilate the lungs of a manikin using a facemask and then position a supraglottic airway device (LMA‐Supreme™) and ventilate the lungs. This process was then repeated on anaesthetised patients, with standard ventilator settings to assess adequacy of ventilation. Sixty‐three students participated in the manikin study. The success rate for ventilating the lungs was 100% for both devices, but the mean (SD) time to achieve successful ventilation was 27.8 (24.4) s with the facemask compared with 38.6 (22.0) s with the LMA‐Supreme (p = 0.008). Fifty‐one of the students progressed to the second part of the study. In anaesthetised patients, the success rate for ventilating the lungs was lower for the facemask, 27/41 (66%) compared with the LMA‐Supreme 37/41 (90%, p = 0.006). For 26 students who succeeded with both devices, the tidal volume was lower using the facemask, 431 (192) ml compared with the LMA‐Supreme 751 (221) ml (p = 0.001), but the time to successful ventilation did not differ, 60.0 (26.2) s vs 57.3 (26.6) s (p = 0.71). We conclude that the results obtained in manikin studies cannot be transferred directly to the clinical situation and that guidelines should take this into account. Based on our findings, a supraglottic airway device may be preferable to a facemask as the first choice for inexperienced emergency caregivers.